1998
DOI: 10.1046/j.1365-2265.1998.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalaemia during insulin‐induced hypoglycaemia in hypopituitary adults with and without growth hormone deficiency

Abstract: Insulin-induced hypoglycaemia causes similar degrees of significant hypokalaemia in patients with normal pituitary function and in those with GH deficiency, either alone or in combination with other pituitary hormone deficiencies. Therefore, insulin-induced hypoglycaemia does not appear to be associated with any greater risk of hypokalaemia in hypopituitary adults with GHD compared to those with normal anterior pituitary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…In our study, insulin use alone or in combination with oral medications was associated with a >2.5-fold–increased risk of cardiovascular events. These findings are consistent with Currie et al (15), which identified a lower survival rate in insulin users compared with oral medication users. The mechanism for the excess risk associated with insulin and sulfonylurea use is not clearly understood; however, it is possible that hypoglycemia plays a role.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, insulin use alone or in combination with oral medications was associated with a >2.5-fold–increased risk of cardiovascular events. These findings are consistent with Currie et al (15), which identified a lower survival rate in insulin users compared with oral medication users. The mechanism for the excess risk associated with insulin and sulfonylurea use is not clearly understood; however, it is possible that hypoglycemia plays a role.…”
Section: Discussionsupporting
confidence: 92%
“…The mechanism for the excess risk associated with insulin and sulfonylurea use is not clearly understood; however, it is possible that hypoglycemia plays a role. It has been proposed that hypoglycemia may precipitate cardiac arrhythmias through hypokalemia and sympatho-adrenal activation (15,16). In addition, glucose variability has been implicated as a factor in oxidative stress and vascular inflammation (17).…”
Section: Discussionmentioning
confidence: 99%
“…All but one developed acute hypokalaemia within 30 min, which lasted for almost 2 h. Ratzmann and Zoellner [11] reported a mean decrease of serum potassium by 0.8 mmol/l during ITT in short healthy children. Comparable results were observed in adults by Davies et al [12]and by Strakosch et al [13]. In all these studies glucose administration, which may exaggerate hypokalaemia, was not performed.…”
Section: Discussionsupporting
confidence: 56%
“…The need for an underlying predisposing genetic or epigenetic condition, resulting in an ionic transmembrane electrolyte imbalance (7,20), has been shown for HypoPP associated with thyreotoxicosis and may partly explain why HypoPP does not occur in all patients with GH deficiency. The need for a predisposing genetic factor is also suggested by a previous study showing that insulin-induced hypoglycemia is not associated with an increased risk of hypokalemia among hypopituitary adults with GH deficiency compared to individuals with normal anterior pituitary function (21).…”
Section: R Lanzi Sc Previtali V Sansone Et Almentioning
confidence: 91%